Economical and social consequences of accidents at work and occupational diseases - Šukys, Ritoldas; Čyras, Petras; Jakutis, Algirdas; Stankiuviene, Aušra (Technological and Economic Development of Economy, 2004)
The main purpose of this scientific research is to estimate social and economical consequences of accidents at work and occupational diseases and prepare recommendations to avoid negative economical and social consequences. To achieve this purpose the methods of selection, poll, statistical analytical and mathematical modeling methods were used. The analysis of present workers health was accomplished and safety conditions in separate economic areas were estimated. Manufacturing, building, agricultural economy and transport companies were studied more detailed. Estimating economical consequences of accidents at work and occupational diseases these expenses were estimated:• Paid by social insurance regarding accidents and occupational diseases per year.• The missed days at work regarding accidents and occupational diseases.• Losses of working capacity are:• Regarding serious accidents per year;• Regarding serious accidents during time left until retirement;• Regarding occupation diseases per year;• Regarding occupation diseases during time left until retirement.A loss in these companies makes 74% of all losses, because of accidents and occupational diseases in Lithuania's economy. After summarizing the results of this research, social and economical consequences of accidents and occupational diseases at work were estimated in separate economical areas and in the whole country. Recommendations for social consequences of occupational disability are given.Article in Lithuanian.Profesinių ligų bei nelaimingų atsitikimų darbe ekonominės ir socialinės pasekmėsFirst Published Online: 21 Oct 2010